Missing pieces, new patterns: the impact of association football international call-ups on team offensive and defensive performance indicators - Campos, João; Gonçalves, Bruno; Travassos, Bruno; Mateus, Nuno; Lengua, Rafael Ballester; Figueira, Bruno; Olthof, Sigrid; Coutinho, Diogo (Frontiers in Psychology, 2026)
IntroductionTo examine how mid-season international call-ups (AFCON and AFC Asian Cup) affect club performance across offensive, defensive, and playing-style key performance indicators (KPIs).MethodsA non-participant observational study analyzed 522 league matches from 58 teams in Europe’s top five leagues (2023–2024). For teams losing players to international duty (n = 130 players across positions), club matches were grouped into three phases: PRE (three matches before), INT-CUP (three during absences), and POST (three after return). Wyscout-derived KPIs covered ball possession, goal scoring, offensive play, set pieces, and defensive actions. Non-parametric repeated-measures ANOVA (p < .05) and Cohen’s d quantified differences.ResultsINT-CUP showed clear improvements in ball-possession KPIs versus PRE and POST: higher total, successful, frontal, lateral, and backward passes; more progressive and deep completed passes; more crosses; and greater passes per possession, alongside shorter average passing length (all p ≤ .05; small–moderate effects). Goal-scoring output increased during INT-CUP (more shots, shots on target—including from outside the box—and goals vs PRE; more goals vs POST; p ≤ .05). Offensive penetration also rose (penalty-area entries and area touches; p ≤ .05), and positional attacks ending in shots were more frequent during INT-CUP (p = .015). Set-piece KPIs did not differ meaningfully. Defensively, PRE exceeded POST in duels, duels won, and defensive duels (p ≤ .05), while conceded goals were broadly unchanged across phases.DiscussionContrary to expectations, international absences coincided with a more possession-oriented style and enhanced attacking output, without compromising defensive outcomes. Effects between PRE and POST were modest, suggesting tactical adaptations during absences can sustain or even improve offensive efficiency. Coaches may leverage forced rotations to explore possession-based structures that preserve defensive stability.